The Potential Role of miRNAs in Cognitive Frailty - Carini, Giulia; Musazzi, Laura; Bolzetta, Francesco; Cester, Alberto; Fiorentini, Chiara; Ieraci, Alessandro; Maggi, Stefania; Popoli, Maurizio; Veronese, Nicola; Barbon, Alessandro (Frontiers in Aging Neuroscience, 2021)
Frailty is a condition, common among the elderly, which has been defined as a state of enhanced vulnerability to stressors, leading to a limited capacity to meet homeostatic demands. Cognitive deficits are also frequent in elderly people, often accompanying frailty. Age is the main independent risk factor for both frailty and cognitive disorders, and compelling evidence suggests that similar age-associated mechanisms could underlie both clinical conditions. Accordingly, it has been suggested that frailty and cognitive impairments share common pathways, and some authors proposed “cognitive frailty” as a single complex phenotype. Nevertheless, so far, no clear common underlying pathways have been discovered for both conditions. MicroRNAs (miRNAs) have emerged as key fine-tuning regulators in most physiological processes, as well as pathological conditions. Importantly, miRNAs have been proposed as both peripheral biomarkers and potential molecular mechanisms involved in physiological and pathological aging. In this review, we discuss the evidence linking changes of selected miRNAs expression with frailty and cognitive disorders. Overall, miR-92a-5p and miR-532-5p, as well as other miRNAs implicated in pathological aging, should be investigated as potential biomarkers (and putative molecular effectors) of cognitive frailty.